A high ratio of linoleic acid (n-6 PUFA) to alpha-linolenic acid (n-3 PUFA) adversely affects early stage of human neuronal differentiation and electrophysiological activity of glutamatergic neurons in vitro - Dec, Karolina; Alsaqati, Mouhamed; Morgan, Joanne; Deshpande, Sumukh; Wood, Jamie; Hall, Jeremy; Harwood, Adrian J. (Frontiers in Cell and Developmental Biology, 2023)
There is a growing interest in the possibility of dietary supplementation with polyunsaturated fatty acids (PUFAs) for treatment and prevention of neurodevelopmental and neuropsychiatric disorders. Studies have suggested that of the two important classes of PUFAs, omega-6 (n-6) and omega-3 (n-3), n-3 PUFAs support brain development and function, and when used as a dietary supplement may have beneficial effects for maintenance of a healthy brain. However, to date epidemiological studies and clinical trials on children and adults have been inconclusive regarding treatment length, dosage and use of specific n-3 PUFAs. The aim of this study is to generate a simplified in vitro cell-based model system to test how different n-6 to n-3 PUFA ratios affect human-derived neurons activity as a cellular correlate for brain function and to probe the mechanism of their action. All experiments were performed by use of human induced pluripotent stem cells (iPSCs). In this study, we examined the effect of different ratios of linoleic acid (n-6) to alpha-linolenic acid in cell growth medium on iPSC proliferation, generation of neuronal precursors and electrophysiology of cortical glutamatergic neurons by multielectrode array (MEA) analysis. This study shows that at a n-6:n-3 ratio of 5:1 PUFAs induce stem cell proliferation, generating a large increase in number of cells after 72h treatment; suppress generation of neuronal progenitor cells, as measured by decreased expression of FOXG1 and Nestin in neuronal precursor cells (NPC) after 20 days of development; and disrupt neuronal activity in vitro, increasing spontaneous neuronal firing, reducing synchronized bursting receptor subunits. We observed no significant differences for neuronal precursor cells treated with ratios 1:3 and 3:1, in comparison to 1:1 control ratio, but higher ratios of n-6 to n-3 PUFAs adversely affect early stages of neuronal differentiation. Moreover, a 5:1 ratio in cortical glutamatergic neurons induce expression of GABA receptors which may explain the observed abnormal electrophysiological activity.